(untitled) (Neo Science Peer Reviewed Journal, 2024)
This systematic review critically examines the influence of digital health tools on patient outcomes, synthesizing existing literature from diverse sources. The review highlights the transformative potential of digital technologies, including mobile health applications, telehealth platforms, and wearable devices, in enhancing patient engagement, adherence to treatment regimens, and clinical outcomes, particularly for individuals with chronic conditions. However, it also emphasizes the significance of contextual factors, such as patient demographics, technological proficiency, and socioeconomic status, which can affect the effectiveness of these interventions. The findings underscore the necessity for healthcare practitioners and policymakers to address access disparities and digital literacy to optimize the integration of digital health tools within healthcare systems. Overall, this review provides valuable insights into the potential benefits and limitations of digital health technologies, guiding future research and implementation strategies aimed at improving patient care.